Decision Making and Patronage Behaviour in Islamic Co-operatives in Aceh, Indonesia - Majid, M. Shabri Abd; Faisal, Faisal; Fahlevi, Heru; Hafasnuddin, Hafasnuddin (Universitas Negeri Semarang, 2021)
Although the number of Islamic co-operatives' memberships only amounted to 2.51 million people (11.19%) to the total membership of co-operatives in Indonesia nationwide, but it has shown a rising trend in its membership by 76.11% over the last decade (Ministry of Co-Operatives SMEs, 2019). These figures raise an essential research question: what drives the decision of Indonesian citizens to patronage Islamic co-operatives? Specifically, this study explores pertinent determinants of decision-making made by the members to select Islamic co-operatives in Aceh, Indonesia. A number of 280 members and non-members of Islamic co-operatives were selected as the sample of the study using a purposive sampling technique. Based on the logistic multiple regression technique, the study recorded that the members' decision-making in selecting Islamic co-operatives was mainly determined by their shari'ah compliance and characteristics' uniqueness. Meanwhile, physical facilities and services quality provided by the Islamic co-operatives have insignificant effects on the people's decision-making to become the memberships of Islamic co-operatives. This empirical evidence suggested that to attract more memberships, the Islamic co-operatives should improve their shari'ah compliance and characteristics' uniqueness.